PENGEMBANGAN MEDIA KARUTA DALAM PEMBELAJARAN KANJI PADA MAHASISWA PENDIDIKAN BAHASA JEPANG TINGKAT II (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out what procedures that carried out in developing karuta media and it already standardized by experts or validators so it’s suitable for media learning. This study uses a research and development model of R&D using the Sugiyono model. The subjects of this study were 25 students of the Japanese Language Education Study Program level II. The collected data were analyzed using questionnaires. The results of the research are based on six stages: a) Potential Problems b) Data Collecting, c) Product Design, d) Product Validation, e) Product Trial. The eligibility level of karuta media is based on an assessment by 2 validators which consist material experts and media experts. Karuta media is eligible based on validation result by material experts with an average score of 75% in the appropriate category, and then media experts with an average score of 90% in the very appropriate category. The product should be revised according to suggestions and input from the experts. Karuta media was tested on students of the Japanese Language Education Study Program level II with 81.2% in the very appropriate category for kanji learning.Key Words: Karuta, Kanji, Japanese language education.